How Can Specialist Advice Influence the Neuroimaging Practice for Childhood Headache in Emergency Department? - Alberto M. Cappellari; Gaia Bruschi; Gisella B. Beretta; Maria T. Molisso; Giuseppe Bertolozzi (MDPI AG, 2023)
Differentiating between primary and secondary headaches can be challenging, especially in the emergency department (ED). Since symptoms alone are inadequate criteria for distinguishing between primary and secondary headaches, many children with headaches undergo neuroimaging investigations, such as brain CT and MRI. In various studies, the frequency of neuroimaging utilization is influenced by several factors, including teaching status, ownership, metropolitan area, insurance status, and ethnicity of patients. However, only a few studies have considered the role of specialist consultations in ordering neuroimaging studies on childhood headaches. We report the contributions of different specialists to the evaluation of children with headaches admitted to the ED and their influence on neuroimaging decisions. We retrospectively reviewed the medical reports of paediatric patients who presented with headaches to the paediatric ED of the Ospedale Maggiore Policlinico of Milano between January 2017 and January 2022. Overall, 890 children with headaches were evaluated (mean age: 10.0 years; range: 1 to 17 years). All patients were examined by the ED paediatricians, while specialist consultations were required for 261 patients, including 240 neurological (92.0%), 46 ophthalmological (17.6%), and 20 otorhinolaryngological (7.7%) consultations. Overall, 173 neuroimaging examinations were required, of which 51.4 and 48.6% were ordered by paediatricians and neurologists, respectively. In particular, paediatricians required 61.4% of brain CT scans, and neurologists required 92.0% of brain MRI scans. In conclusion, paediatricians were responsible for the management of most children with headaches admitted to the ED, while specialist consultations were required only in about a third of the cases. Although there was no significant difference in the number of neuroimaging studies ordered by specialists, brain CT scans were most often used by paediatricians, and MRI scans by neurologists.